PEMBINAAN KEAGAMAAN PESERTA DIDIK MUSLIM OLEH GURU PENDIDIKAN AGAMA ISLAM (PAI) DI YAYASAN KHATOLIK - Gesti Puspitasari; Misyuraidah Misyuraidah; Muhammad Fauzi; Syarnubi Syarnubi (PAI RAFAH, 2019)
Indonesia passed Law No. 20 of 2003 concerning the National Education System, which in Article 12 paragraph 1 of the Law states that: "Every student has the right to get religious education according to the religion he follows." The purpose of this study is to determine the religious formation of Muslim students by teachers Islamic Religious Education, factors supporting and inhibiting religious formation by Islamic Religious Education (PAI) teachers at the Catholic Foundation of SANTO LOUIS Middle School, Muara Padang District, Banyuasin Regency. This research is a qualitative research field (field research), which describes the religious guidance of Muslim students by Islamic Religious Education teachers. The type of research approach used in this research is descriptive qualitative with methods of collecting data through observation, interviews, documentation. Data were analyzed qualitatively through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study are religious coaching by Islamic Religious Education teachers conducted in the classroom which includes: Muslim students are accustomed to praying, accustom to saying "Assalamualaikum", getting used to shaking hands with the teacher, accustoming students to throw trash in their place, every day Friday male students are required to attend Friday prayers at the mosque. Factors supporting religious guidance by Islamic Religious Education teachers include the availability of time, place and facilities for learning infrastructure, support from parents of students, support from Muslim and non-Muslim students, support from teachers and foundations. The limiting factor is the limited monitoring of student behavior when outside school hours, there are still some Muslim students who have not been able to read Arabic letters, there is no mosque at SMP SANTO LOUIS teachers who teach PAI lessons are not teachers who have taken PAI higher education but have never been through PAI religious education or reciting at the Miftahul Huda Islamic boarding school.